Bone Mineral Density in Children with Cerebral Palsy: Associations with Anthropometric and Clinical Characteristics—A Cross-Sectional Study - Aqeelah Abdulelah Aljishi; Mohammed A. Al-Omari; Ayat H. Al Safar; Shahad A. AlHazzaa; Alaa I. Ibrahim (Children)
Background/Objectives: Cerebral palsy (CP) is the most common cause of neurological disability in children and is frequently associated with low bone mineral density (BMD) and increased risk of fractures. This study aimed to assess BMD in children with CP, compare it with normative standards, and explore potential associations with anthropometric parameters and the clinical characteristics of children with CP. Methods: Thirty-six children with CP aging 6–15 years from both sexes with varying levels of Gross Motor Functional Classification System (GMFCS) and spasticity were evaluated. Areal BMD and Z-scores (total and subtotal) were measured using dual-energy X-ray absorptiometry (DXA). Regression analysis identified predictors of BMD. Results: Children with GMFCS levels III–V had significantly lower total and subtotal Z-scores compared to those with levels I–II (p = 0.001 and p = 0.02, respectively). Total Z-score was significantly predicted by weight (β = 1.02, p = 0.002), height (β = −0.72, p = 0.02), and sedentary time (β = −0.47, p = 0.005). “No walking” was the only significant predictor for subtotal Z-score (β = −0.50, p = 0.004). Conclusions: Children with moderate to severe CP exhibited significantly lower BMD, particularly those with limited ambulation and higher spasticity levels. These findings underscore the importance of early screening and targeted interventions to optimize bone health in this population.